Bavachalcone Enhances RORα Expression, Controls Bmal1 Circadian Transcription, and Depresses Cellular Senescence in Human Endothelial Cells - Dang, Yanqi (Hindawi Publishing Corporation, 2015)
The circadian clock regulates many aspects of (patho)physiology in the central nervous system and in the peripheral tissues. RAR-related orphan receptor α (RORα), an orphan nuclear receptor, is involved in circadian rhythm regulation, including regulation of cardiovascular function. Bavachalcone, a prenylchalcone, is a major bioactive chalcone isolated from Psoralea corylifolia. This natural ingredient activated RORα1 luciferase reporter activity on drug screening. In addition, bavachalcone induced RORα1 expression in mRNA and protein levels in a dose-dependent manner and enhanced the circadian amplitude of Bmal1 mRNA expression after serum shock. Moreover, bavachalcone suppressed senescence in human endothelial cells and mRNA expression of p16ink4a (a marker of replicative senescence) and IL-1α (a proinflammatory cytokine of the senescence-associated secretory phenotype). These inhibitory effects were partially reversed by the RORα inhibitor VPR-66. Our results demonstrate that bavachalcone, as a natural medicine ingredient, has a pharmacological function in regulating RORα1.